'Here, We Take the Indian out of Them': Pentecostalism and Mestizaje in Mexico City. Issue 2 (4th May 2018) - Aguilar de la Cruz, Hedilberto
ABSTRACT: This work focuses on ideological and cultural miscegenation among Pentecostal indigenous groups in Mexico City, paying attention to the socio-historical development of Pentecostalism and studies on mestizaje of the last three decades. It analyzes the relationship between urban Pentecostalism and mestizaje as a socio-cultural whitening process, facilitated by specific religious practices. Socially conservative Pentecostal churches foment Mexican nationalism and provide a mechanism of urban social integration for indigenous immigrants with precarious employment and low levels of education. Their participation in Pentecostal congregations helps indigenous subjects to face the hardships inscribed in their social condition with greater success. At the same time, the religious socialization discourse of Pentecostal churches associates some aspects of indigenous ethnic belonging with the symbolic element of 'sin'. This association leads to a process of ethnic de-characterization that gradually instills a culture of mestizaje indianizado (indianized miscegenation). In this way, indigenous Pentecostals are induced to deny their sinful life of the past and embrace a new life in Christ – a religious message embedded in an ideology that negates the ethnicity of the faithful and coerces them into a 'modernization' of identity in the face of a 'hostile world'.